2003
DOI: 10.1557/proc-793-s10.3
|View full text |Cite
|
Sign up to set email alerts
|

The Synthesis of Ce-Filled CoSb3 and Characterization of its Magnetic and Structural Properties

Abstract: A series of cerium-containing CoSb3 samples were synthesized, with cerium quantities varying from 0 to 2 stoichiometric equivalents. These samples were annealed at low temperatures to crystallize the kinetically stable phases CexCo4Sb12 (x = 0–0.5). X-ray diffraction showed that these samples were phase pure, and Rietveld analysis on x-ray diffraction data from powder samples indicated that these samples were 25–88% crystalline. Electrical measurements showed that these samples are n-type, which was previously… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…The series of Ce x Co 4 Sb 12 samples was synthesized with x = 0 to 2, based on EPMA analysis, and analyzed fully elsewhere [2]. The sample compositions were normalized to full filling of the metal site.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The series of Ce x Co 4 Sb 12 samples was synthesized with x = 0 to 2, based on EPMA analysis, and analyzed fully elsewhere [2]. The sample compositions were normalized to full filling of the metal site.…”
Section: Resultsmentioning
confidence: 99%
“…The samples were X-ray amorphous as deposited, but crystallized when heated to moderate temperatures (200 -300 °C), and showed only the skutterudite phase in the X-ray diffraction scans. 2 increased as more cerium was included in the sample (see Table I). We observed several trends in the data: first, that the lattice size increased with increasing amount of cerium content (see Table II).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Besides, the thin film CoSb 3 sample prepared by deposition experienced increased Ce-filling fraction. Smalley et al [41] reported a high Ce-filling fraction of ~0.55 in deposited CoSb 3 film.…”
Section: Introductionmentioning
confidence: 99%